Inflation and Broadband Revisited: Evidence from an OECD Panel. A replication study of Yi and Choi (Journal of Policy Modeling, 2005) - Klaus Friesenbichler (International Journal for Re-Views in Empirical Economics (IREE), 2018)
This note revisits the conjecture that the use of broadband internet lowers transaction costs and thereby inflation. Using a macro-economic panel of OECD countries, it replicates and expands previous estimations by Yi and Choi (2005). We confirm the direction of the results, but also highlight a series of conceptual and econometric issues in the original contribution that need to be addressed.
http://dx.doi.org/10.15456/iree.2018103.094134
Keywords: E31; O1; O3; 330; inflation; broadband